On the Primary Water Radicals’ Production in the Presence of Gold Nanoparticles: Electron Pulse Radiolysis Study - Viacheslav Shcherbakov; Sergey A. Denisov; Mehran Mostafavi (Nanomaterials, 2020)
Gold nanoparticles are known to cause a radiosensitizing effect, which is a promising way to improve radiation therapy. However, the radiosensitization mechanism is not yet fully understood. It is currently assumed that gold nanoparticles can influence various physical, chemical, and biological processes. Pulse radiolysis is a powerful tool that can examine one of the proposed effects of gold nanoparticles, such as increased free radical production. In this work, we shed light on the consequence of ionizing radiation interaction with gold nanoparticles by direct measurements of solvated electrons using the pulse radiolysis technique. We found that at a therapeutically relevant gold concentration (<3 mM atomic gold, <600 μg × cm−3), the presence of gold nanoparticles in solution does not induce higher primary radicals’ formation. This result contradicts some hypotheses about free radical formation in the presence of gold nanoparticles under ionizing radiation previously reported in the literature.